'

Proste równania wykładnicze

Wprowadzenie

$latex {{a}^{x}}={{a}^{y}}\Leftrightarrow x=y$

Przykład 1

Rozwiąż równania:
a) $latex {{\left( {\frac{1}{3}} \right)}^{\text{x}}}=\frac{1}{{81}}$
b) $latex {{2}^{\text{x}}}=16$
c) $latex {{\left( {\frac{2}{3}} \right)}^{\text{x}}}=0$
d) $latex {{\left( {1\frac{1}{2}} \right)}^{\text{x}}}=1$

Przykład 2

Rozwiąż równania:
a) $latex {{3}^{{{{\text{x}}^{2}}+2}}}=27$
b) $latex {{\left( {\frac{5}{2}} \right)}^{{{{\text{x}}^{2}}-3\text{x}}}}={{\left( {\frac{4}{{25}}} \right)}^{{\text{x}-3}}}$
c) $latex {{\left( {\frac{1}{2}} \right)}^{{\frac{\text{x}}{{\text{x}-1}}}}}={{\left( {\frac{1}{{64}}} \right)}^{{\frac{1}{{\text{x}+2}}}}}$
d) $latex {{\left( {\frac{1}{2}} \right)}^{{{{\text{x}}^{3}}+{{\text{x}}^{2}}}}}={{\left( {\frac{1}{{32}}} \right)}^{{\text{x}+1}}}$

Przykład 3

Rozwiąż równania:
a) $latex {{5}^{{\text{x}+2}}}\cdot {{25}^{{3\text{x}-1}}}={{125}^{{\text{x}+4}}}$
b) $latex {{2}^{{\text{x}-1}}}\cdot {{\left( {\frac{1}{2}} \right)}^{{2\text{x}-3}}}=8$
c) $latex {{\left( {\frac{1}{3}} \right)}^{{{{\text{x}}^{2}}-\text{x}}}}\cdot {{27}^{\text{x}}}=\frac{{{{3}^{{\text{x}-1}}}}}{{27}}$
d) $latex {{\left( {\frac{2}{3}} \right)}^{{{{\text{x}}^{3}}}}}\cdot {{\left( {\frac{9}{4}} \right)}^{\text{x}}}=\frac{{16}}{{81}}\cdot {{\left( {\frac{4}{9}} \right)}^{{-{{\text{x}}^{2}}}}}$